Uji Bioaktivitas Fraksi Metanol dan Etil Asetat Tumbuhan Paku Sisik Naga (Drymoglossum piloselloides (L) pressl.) Terhadap Bakteri Staphylococcus aureus dan Salmonella typhi - Riza Linda, Rian Juni Sumito, Siti Khotimah, (Universitas Tanjungpura, 2016)
Staphylococcus aureus is a pathogenic bacterium that causes infection to wound, and Salmonella typhi is a bacterium that causes typhoid. The dragon scales (Drymoglossum piloselloides) is one of the plants that can potentially serve as an antibacterial agent. This research aims to find out the class of compound of secondary metabolites and the antibacterial activities of methanol and ethyl acetate fractions of the dragon scales against S. aureus and S. typhi bacteria. The study was conducted for 3 months with a disc diffusion method (Kirbybauer). The concentrations of methanol and ethyl acetate fractions of the dragon scales used in this research were 0,25 g/mL, 0,3 g/mL, 0,35 g/mL, ciprofloxasin 0.005 mg/mL as a positive control and DMSO 10% as a negative control. Research findings showed that the methanol and ethyl acetate fraction contained flavonoidand terpenoid compounds. The methanol fraction of the dragon scales had antibacterial activity against S. aureus bacterium with a strong response at a concentration of 0.25 g/mL while the ethyl acetate fraction had no antibacterial activity against S. aureus and S. typhi bacteria.